EDUKASI GIZI DAN SKRINING STATUS GIZI REMAJA PUTRI DALAM UPAYA PENINGKATAN KESEHATAN REMAJA PESISIR PANTAI, KABUPATEN KUPANGEdukasi gizi dan skrining status gizi remaja putri dalam upaya peningkatan kesehatan remaja pesisir pantai, Kabupaten Kupang - Christina Olly Lada ch (Jurnal Media Tropika, 2022)
The adolescents who are still growing are in a period of transition from childhood to adulthood. Adolescent girls' nutritional status, especially anemia, must be considered, they even need intervention to prepare themselves to be holistically healthy as adults. Adolescent girl who become a mother, need to learn and avoid chronic protein energy deficiency and anemia. They need to be taught to maintain their nutritional status, so when they enter the life cycle, especially in the first 1000 days of life as part of the golden period of child growth and development, they will be well cared for. Of course, this will also reduce the prevalence of stunting under-fives in the future. In this preventive promotive effort, apart from providing adolescent girls with nutrition education, consumption of blood supplement tablets, anemia screening is also carried out by checking blood hemoglobin levels. Habits and awareness of healthy living and good nutritional status are what we want to instill in community service activities for adolescent girl on the coast of Kupang Regency.